(untitled) (Politeja, 2022)
LEADERSHIP OF THE CHIEF JUSTICE OF THE US BASED ON AN ANALYSIS OF THE ACTIVITIES OF JUSTICE JOHN ROBERTS, JR. Chief Justice of the United States is a formal leader of the Supreme Court responsible for supervisinig Court’s administrative work, including his presiding over justices’ conferences and assigning opinion-writing to a justice in the majority. At the same time Chief Justice is representing the Court in relations with other branches of government, including membership in certain judicial institutions, assisting the president during his oath of Office, and presiding over the impeachment process of the chief executive. Called the top judicial officer in the United States, the Chief Justice seems to have enough power not only to lead the Court but also to determine its adjudication, protecting its integrity and impartiality. The reality, however, proves that the model of leadership and the scope of impact of Chief Justices on Court’s functioning depends on several inner and outer factors, therefore not every formal leader of the Court was its real leader. The aim of the analysis is to assess the leadership of Chief Justice John Roberts, who was appointed to the Supreme Court by George W. Bush in 2005 and has held his office until today. Introducing four models of leadership of Chief Justices, the Author is willing to determine the role John Roberts plays in contemporary Court, analyzing the impact of his leadership skills and the circumstances under which he operates as the Chief Justice. The growing significance of the Supreme Court in American social, economic, and political life makes such an analysis even more interesting and necessary